Особенности атрибуции холодного оружия при помощи клейм - Литвинов, В.В. (Культура народов Причерноморья, 2013)
В исследовании раскрываются особенности атрибуции холодного оружия при помощи
клейм. Рассмотрены причины ошибочной атрибуции культурных ценностей. В дослідженні розкриті особливості атрибуції холодної зброї за допомогою клейм.
Розглянуті причини помилкової атрибуції культурних цінностей. The culture values – the various objects material and spiritual culture, which have archaeology,
anthropology, historical, literature, art and scientific values for national and word cultures. The task for
customs officers in skill identification and make an inventory the culture values. There are multitude kinds the
culture values which it is necessary different forms for their description. The weapon is one of kinds the culture
values. The author propose rule for identification given form the weapon brands. The sources of building the
visual thumbnails of the culture values in human are analyzed in this work. The author reasons of mistaking
attribution of cultural values.